Water interaction and water productivity of dairy cattle in Wuchale Wereda, Nile River Basin, Ethiopia - Salehu, T. (Addis Ababa University, 2007)
Livestock interact with the environment directly or indirectly in the process of their production. The interaction with the water resources is also direct or indirect and can be positive or negative depending on the system of production. In the study area of this work, the mixed croplivestock production is the main type of livestock production by smallhoder subsistence farmers where cattle are reared for dairying. The study was done as a case study of two selected PA’s of the wereda. One part of this research was to describe the dairy cattle water interaction. The study has showed that water required for the production of cattle feed was reduced by 2.6*105 m3 per annum because of crop residual feeds. This implies a good water-dairy cattle interaction in the study PA’s of Wuchale wereda. Field measurements, questionnaire surveying and sample water laboratory tests with appropriate statistical analysis were done to complete the description of dairy cattle water interaction. The dairy cattle water productivity evaluation of the two selected PA’s of study area was the second part of this study. The productivity of the two PA’s was 0.41 USD/m3 and 0.14 USD/m3 for the peri urban and rural sample locations respectively. Future improvement aspects of the dairy cattle water productivity were suggested by this work, which all ends up in the sustainable management of the dairy cattle- water interaction in the area.